2011
DOI: 10.1002/bies.201000131
|View full text |Cite
|
Sign up to set email alerts
|

Retinal determination genes function along with cell‐cell signals to regulate Drosophila eye development

Abstract: It is thought that Retinal Determination gene products define the response made to cell-cell signals within the eye developmental field by binding to enhancers of genes that are also regulated by cell-cell signaling pathways. In Drosophila, Retinal Determination genes including Eyeless, teashirt, eyes absent, dachsous and sine oculis, are required for normal eye development and can induce ectopic eyes when mis-expressed. Characterization of the enhancers responsible for eye expression of the hedgehog, shaven, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…For example, enhancer E controls early eya expression while enhancer 1 is responsible for the bulk of late eya transcription (Fig 3). Having separate cis-regulatory elements control eya expression at different times during development is consistent with the idea that RD genes are dynamically regulated temporally and spatially to insure distinct expression patterns necessary for the differentiation of specific retinal cell types over the course of eye development [40]. …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…For example, enhancer E controls early eya expression while enhancer 1 is responsible for the bulk of late eya transcription (Fig 3). Having separate cis-regulatory elements control eya expression at different times during development is consistent with the idea that RD genes are dynamically regulated temporally and spatially to insure distinct expression patterns necessary for the differentiation of specific retinal cell types over the course of eye development [40]. …”
Section: Discussionsupporting
confidence: 68%
“…As such their regulation and gene expression is often highly temporally and spatially dynamic allowing for the proper differentiation of the multiple cell types necessary for the proper function of the compound eye [40]. eyes absent is a core member of this network and provides a key example of this type of complex gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that signaling pathways activated in the morphogenetic furrow increase levels of Eya, So and Dac; furthermore, it is proposed that this upregulation alters their targets, creating an embedded loop within the circuitry governing retinal development and allowing signaling events to indirectly regulate targets through the RD network [26], [28], [61]. The identification of ey regulation by So posterior to the morphogenetic furrow represents a direct target consistent with this model.…”
Section: Discussionmentioning
confidence: 61%
“…ato is first expressed in all cells in a stripe just anterior to the morphogenetic furrow, but it rapidly resolves more posteriorly into regularly spaced groups of cells and then into single cells, the future R8 photoreceptors (Figure (b)). Its initial expression is driven by a 3′ enhancer region that contains essential binding sites for Ey and So, suggesting that the input from Hh and Dpp signaling may be mediated by these eye determination factors . A 5′ enhancer that responds to Ato autoregulation and to the zinc finger transcription factor Roughened eye mediates its later expression .…”
Section: Progressive Photoreceptor Differentiation Is Driven By Autormentioning
confidence: 99%